Effectiveness of Anaemia Therapy in Breast Cancer Patients with Chemotherapy-Induced Anaemia at Dharmais Cancer Hospital Jakarta in 2023 - Muti, Annisa Farida; Yasya Sabrinanissa; Rahmi, Eldiza Puji; Pradana, Dhigna Luthfiyani Citra (Pharmaceutical Journal of Indonesia, 2026)
Introduction: Chemotherapy-induced anemia is a common complication in breast cancer patients, primarily caused by bone marrow suppression, which inhibits erythropoiesis and reduces hemoglobin levels. Effective management of anemia is crucial in improving patients' quality of life and tolerance to cancer therapy. This study aims to evaluate the clinical effectiveness of anemia therapy, including packed red cell (PRC) transfusion and erythropoiesis-stimulating agents (ESA) administration, in breast cancer patients post-chemotherapy at Dharmais Cancer Hospital in Jakarta. Methods: The study design used was a retrospective observational study with data collected from inpatient medical records throughout 2023. A total of 35 patient records were selected using total sampling technique. Hemoglobin levels before and after anemia therapy were analyzed using paired statistical tests to assess the effectiveness of the therapy. Results: The analysis results showed a statistically significant increase in hemoglobin levels after therapy was administered (p < 0.001). Conclusion: indicating that both PRC transfusions and ESA therapy effectively contributed to correcting post-chemotherapy anemia in breast cancer patients.